Petrographic and geochemical study of Doua granitoids (adamawa-yade domain, center Cameroon): Petrogenesis and geodynamic implication - Diguim Kepnamou, Amadou; Seguem, Naimou; Mama, Ntoumbé; Adama Adama Dairou, Amaya; Bienvenu, Bello; Kalaza Josue, Haskandi; Wangmene Salomon 5, Ngounouno Ismaila, Awé; Ismaila, Ngounouno (International Journal of Advanced Geosciences, 2022)
The region Doua is located in the central area or Adamawa-Yade domain of the Pan-African fold belt in Cameroon. This work focuses on the petrography and geochemistry of granitoids in this region. The study area is made up of plutonic rocks (amphibole and biotite granite, biotite and muscovite granite, syeno-diorite, syenite. The geochemical study of the granitoids in the area shows that the rocks are magnesian and slightly iron-bearing, potassic to hyper-potassic calc - alkaline, metaluminous and belongs to type I granitoids. The profiles of the rare earths (REE) show a negative anomaly in Eu. The multi-element spectra show positive anomalies, or negative anomalies for some samples in Ba and Negative anomalies in Nb-Ta, Sr and Ti. The process which led to the formation of these rocks is fractional crystallization. These rocks are setup in a syn-collisional subduction environment (volcanic arc granitoids).